A reassessment of the risk of multiple sclerosis developing in patients with optic neuritis after extended follow-up. Issue 6 (June 1987) - Francis, D A; Compston, D A; Batchelor, J R; McDonald, W I
Abstract : One hundred and one of 146 patients presenting with isolated idiopathic optic neuritis, previously reviewed in 1978, were reassessed clinically, and retyped for HLA antigens and Factor B alleles, after a mean follow-up of 11.6 years. Fifty eight patients (57%) had developed multiple sclerosis at the time of reassessment in the present study, of whom 51 (88%) had clinically definite disease. This compared with 40% of the original group, in 1978, of whom 62% then had clinically definite multiple sclerosis. When the life-table method of analysis was used, the probability of developing multiple sclerosis was 75%, 15 years after the initial episode of optic neuritis. The frequencies of HLA-DR2 and the recently defined D-region antigen, DQw1, were significantly increased in patients with isolated optic neuritis and those who subsequently developed multiple sclerosis compared with normal controls, but neither allele appears to influence progression from optic neuritis to multiple sclerosis. Patients with optic neuritis who were HLA-DR3 positive had an increased risk for the development of multiple sclerosis (RR = 2.8) and this risk was further enhanced when DR3 occurred in combination with DR2 (RR = 6.7). The overall increased risk of developing multiple sclerosis for patients with this combination was 26 times that for the normal population. When the patients' original tissue-typing was considered BT 101 no longer influenced conversion of optic neuritis to multiple sclerosis. This may partly be explained by improved methods of tissue-typing, since not all BT 101 patients were subsequently found to be positive for HLA-DR2 or HLA-DQw1 and vice versa and by extended follow-up as multiple sclerosis conversion in HLA-DR2 negative individuals increased with time. All 101 patients were typed for Factor B alleles. No significant differences in frequencies were found between individuals with isolated optic neuritis or those who progressed to multiple sclerosis compared with the control population. Recurrent episodes of optic neuritis were associated with an increased risk for the development of multiple sclerosis in this study.